Is melancholia a distinct syndrome? Recurrence, chronicity, and severity give evidence in the 50 year follow-up of the Lundby Study - Nöbbelin, Linnéa; Bogren, Mats; Mattisson, Cecilia; Westling, Sofie; Brådvik, Louise (Frontiers in Psychiatry, 2023)
Whether melancholia is a distinct syndrome has long been debated. One aspect of a valid syndrome is whether it allows for determination of a prognosis. The aim of this study is to investigate the course of melancholic depression versus non-melancholic depression with a focus on: i) time to and probability of recovery from the first depressive episode, ii) time to and risk of the first recurrence, iii) rate of recurrence, iv) time with depression or antidepressant medication, and v) suicide risk. The Lundby Study is a longitudinal community study on mental health that followed a geographically defined population (N=3563) for up to 50 years, 1947-1997. Subjects with first onset depression were assessed as melancholic (N=46) or non-melancholic (N=381) using the DSM-IV melancholic specifier. These diagnoses were made in retrospect using all available information from semi-structured interviews by psychiatrists, key informants, registers, and patient records. We found no significant difference between melancholic-and non-melancholic depression in time to and probability of recovery from the first depressive episode. The time to first recurrence was shorter in melancholic than in non-melancholic depression and the risk of first recurrence for the melancholic group was 2.77 (95% confidence interval [CI] 1.83-4.20) times the risk in the non-melancholic group. The median rate of recurrence was higher in the melancholic group, at 0.19 recurrences per year at risk (interquartile range [IQR] 0.08-0.47), compared to the non-melancholic group, at 0.10 recurrences per year at risk (IQR 0.05-0.21) (p<0.03). The median percentage of time being depressed or on antidepressant medication was higher in the melancholic group, 17% (IQR 3 -20%), compared to the non-melancholic group, 8% (IQR 7-33%) (p<0.001). The risk of suicide was higher in the melancholic group, hazard ratio 4.13 (95% CI 1. 49-11.48, p<0.01). To conclude, melancholic depression had a more recurrent, chronic, and severe course with a higher suicide risk than did non-melancholic depression in the Lundby population. Although our use of retrospective diagnosis might limit interpretation of results, the findings indicate that melancholia may be useful in determining prognosis and may be a valid psychopathological syndrome.